Apple osmotic dehydration described by three-dimensional numerical solution of the diffusion equation. Issue 16 (10th December 2018) - Aires, Kalina Lígia Cavalcante de Almeida Farias; da Silva, Wilton Pereira; de Farias Aires, Juarez Everton; da Silva Júnior, Aluízio Freire; Silva, Cleide Maria Diniz Pereira da Silva e
ABSTRACT: In the present study, experimental data of osmotic dehydration kinetics of apple, cut into slices with parallelepiped shape, were simulated using two types of diffusion models. Model 1 considers the constant values of mass diffusivities and volume of the slices. Model 2, on the other hand, considers variable mass diffusivities and also the shrinkage of the product. The numerical solution of the three-dimensional diffusion equation in Cartesian coordinates was obtained through the finite volume method, with a fully implicit formulation and boundary condition of the first kind. Process parameters were determined by optimization using the experimental data sets, through the minimization of an objective function, called χ 2 . The results of the osmotic dehydration kinetics were compatible with those of other studies found in the literature. Process temperature and osmotic solution concentration had influence on the phenomenon, but temperature was preponderant. A study was conducted on water and sucrose distribution during the osmotic dehydration. The results obtained through the mathematical model that considered the variable diffusivity and shrinkage showed greater adequacy to the experimental data.